2002
DOI: 10.1002/pola.10461
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation polymerization of aniline in the presence of water‐soluble organic acids

Abstract: The precipitation polymerization of aniline in the presence of organic acids, including toluene‐4‐sulfonic acid, phenylphosphonic acid, 4‐aminophenylphosphonic acid, and acetophosphonic acid, led in one step to conductive polyaniline. The polyaniline showed very good affinity for water and was easily modified to be water‐soluble. In comparison with the widely studied postpolymerization of doped polyaniline, this reaction allowed reasonably good conductivity to be achieved at a lower acid/polyaniline ratio. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Actually the term precipitation polymerization has been utilized long time ago, but it has not attracted much attention because of difficulty to control particle uniformly. [36][37][38] Precipitation polymerization was first reported by the Sto ¨ver group in 1993. 30 Distillation-precipitation polymerization 39 (in 2004) and photo-initiated precipitation polymerization 40 (in 2007) have subsequently been developed based on the improvement of precipitation polymerization.…”
Section: Types Of Precipitation Polymerizationmentioning
confidence: 99%
“…Actually the term precipitation polymerization has been utilized long time ago, but it has not attracted much attention because of difficulty to control particle uniformly. [36][37][38] Precipitation polymerization was first reported by the Sto ¨ver group in 1993. 30 Distillation-precipitation polymerization 39 (in 2004) and photo-initiated precipitation polymerization 40 (in 2007) have subsequently been developed based on the improvement of precipitation polymerization.…”
Section: Types Of Precipitation Polymerizationmentioning
confidence: 99%
“…The peaks at 480 nm can be assigned to the localized polaron, which are the characteristics of the protonated polyaniline [24]. The presence of the broad band at higher wavelength represents the extended coil conformation [31]. Thus it may be concluded that UV-VIS spectra indicate the dominance of polaron structure of the PANI in concentrated H 2 SO 4 solution.…”
Section: Sample Preparation and Characterization Techniquesmentioning
confidence: 96%
“…Whereas the use of a convenient steric stabilizer, such as poly(methyl vinyl ether), poly(vinyl alcohol‐ co ‐acetate), cellulose ethers, poly( N ‐vinylpyrrolidone), and so on is a feasible route to aqueous dispersion of PANI, postelimination of the hydrophilic stabilizer from the system is needed in view of corrosion protection. An alternative method consists of polymerization of aniline in an emulsion comprising water, an hydrosoluble oxidizing agent (typically APS) and a nonpolar or weakly polar organic solvent (xylene, chloroform, or toluene) in the presence of a functionalized protonic acid (such as dodecylbenzenesulfonic acid) which acts simultaneously as a surfactant and as a protonating agent for the resulting PANI . When the reaction was performed in the solid state at −10 °C, the diffusion of aniline from droplets to micelles was suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method consists of polymerization of aniline in an emulsion comprising water, an hydrosoluble oxidizing agent (typically APS) and a nonpolar or weakly polar organic solvent (xylene, chloroform, or toluene) in the presence of a functionalized protonic acid (such as dodecylbenzenesulfonic acid) which acts simultaneously as a surfactant and as a protonating agent for the resulting PANI. [11][12][13][14][15] When the reaction was performed in the solid state at 210 C, the diffusion of aniline from droplets to micelles was suppressed. Therefore, aniline droplets play a "templatelike" function in the formation of hollow microspheres.…”
mentioning
confidence: 99%